Political action as a methodological tool to implement proposals: A critical-participatory research case study. - Godínez Mora, Andrés (2017)
The following paper summarizes the theoretical aspects that originated the methodological tool called “political action” for researches that requires changes in the daily lives of the participants of the project and their context. The base research of this paper was based on the construction of political culture using anime series, besides it sought to promote critical thinking that would be reflected in works of manga drawing. According to the above, the development of proposals to raise awareness about different problems from a group participatory methodology. The main findings demonstrated the viability of such projects and the applicability in other types of research and topics. In addition, this allowed to observe the application of knowledge gained from previous experiences and the development of methods to apply this.